2018
DOI: 10.3390/agriculture8080117
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Relationships in Legume Crops Are Plant-Microorganism-Specific and Strongly Influenced by Salinity

Abstract: This study investigated the effects of specific strains of two arbuscular mycorrhizae fungi (AMF) (Rhizophagus irregularis and Claroideoglomus claroideum) and of two plant growth-promoting bacteria (PGPB) (Rhizobium leguminosarum and Burkholderia spp.), supplied either individually or as combination of a mixture of both arbuscular mycorrhizae fungi with each bacteria on root morphology, growth and fresh grain yield in pea (Pisum sativum L.) plants. Inoculated and non-inoculated pea plants were subjected to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Also, El-Tantawy and Nawar (2013) found that faba bean plants sprayed with Fe scored significantly the highest total yield (kg/faddan) compared to control treatment. According to our results the effect of interaction between inoculated AMF and foliar Fe concentrations agree with those reported by (Veselaj et al, 2018 andPereira et al, 2019) who showed that the inoculation with AMF improved productivity parameters such as number of pods and weight of pods and seeds, so that increased yield significantly. Also, this result found by Juntahum et al, (2020) who showed an increased productivity in Sugarcane plant by inoculation AMF alone while, the highest plant biomass and productivity were observed in the AMF + 50% P treatment.…”
Section: Disussionsupporting
confidence: 92%
“…Also, El-Tantawy and Nawar (2013) found that faba bean plants sprayed with Fe scored significantly the highest total yield (kg/faddan) compared to control treatment. According to our results the effect of interaction between inoculated AMF and foliar Fe concentrations agree with those reported by (Veselaj et al, 2018 andPereira et al, 2019) who showed that the inoculation with AMF improved productivity parameters such as number of pods and weight of pods and seeds, so that increased yield significantly. Also, this result found by Juntahum et al, (2020) who showed an increased productivity in Sugarcane plant by inoculation AMF alone while, the highest plant biomass and productivity were observed in the AMF + 50% P treatment.…”
Section: Disussionsupporting
confidence: 92%
“…In addition, this research also confirmed that there are significant relationships between the AMF development, Glomus community structure and fruit quality attributes (Figure 6). The increases in the fruit TSS, SS, OA, VC, and SP were positively associated [62], while the Fusarium suppression and reduction in nitrate concentration were negatively correlated with the enriched Glomus taxon [63]. These interactions were most likely attributable to the fact that the greatest colonization, spore germination and hyphal growth of Glomus species followed by Funneliformis can directly exert an impact on fruit productivity traits, which may be stimulated by the favorable mutualism induced by the treatments applied [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…Plants inoculated with R. laguerreae and coinoculated with AMF presented higher rates of increased of grain yield (in terms of pod length, number of pods and seeds produced, and weight of pods and seeds per pod and yield (Tons/feddan). Also, Veselaj et al, (2018) found that combined application of AMF with R. leguminosarum under saline conditions, resulted a higher yield than the same treatment separately and control. Ravikumar (2012) and Denton et al, (2013) Improvement in grain yield, namely in the number of pods, seeds and weight of seeds, were reported in other studies with rhizobial inoculation in faba bean.…”
Section: Effect Of Biofertilizers Treatments and Some Sinai's Flora Extracts On Yield And Its Components Of Faba Bean Plantmentioning
confidence: 92%